STRATEGI GURU DALAM MENGATASI KESENJANGAN KOGNITIF SISWA DI KELAS YANG MENERAPKAN KURIKULUM MERDEKA - Rosfiani, Okta; Anggreini, Novita; Irmanika, Ananta; Devansyah, Azriel; Hanif, Farhan Nur (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
ABSTRACT The implementation of the Merdeka Curriculum faces challenges in addressing students' cognitive gaps due to teachers' difficulties in differentiated instruction and comprehensive diagnostic assessment, necessitating innovative strategies to enhance teacher competence for achieving the curriculum's project-based learning goals. This qualitative research examines teacher strategies in overcoming students' cognitive gaps in classes implementing the Independent Curriculum, with a case study at MA Darussalam, South Tangerang City, Banten Province, class 10. Through in-depth interviews with 1 PAI teacher and 1 principal, as well as learning observations, the study identified four effective strategies: (1) differentiated learning based on diagnostic assessment, (2) continuous formative assessment, (3) project-based learning, and (4) utilization of educational technology. The findings show an increase in student understanding after three months of implementation, with key factors being personal feedback, peer tutoring, and changes in student mindsets. The main obstacles include limited time for material preparation and the need for ongoing teacher training. The implications of the study emphasize the importance of: (1) developing a community of teacher practice, (2) integrating technology into assessment, and (3) school policies that support pedagogical flexibility. These findings provide an operational framework for teachers in managing heterogeneous classes according to the principles of the Independent Curriculum, while enriching the differentiated learning model with local contextualization. The study recommends the development of a digital platform integrated training module to optimize strategies for addressing cognitive gaps. ABSTRAK Implementasi Kurikulum Merdeka menghadapi tantangan dalam kesenjangan kognitif siswa akibat kesulitan guru dalam pembelajaran berdiferensiasi dan asesmen diagnostik, sehingga diperlukan strategi inovatif untuk meningkatkan kompetensi guru demi tercapainya tujuan kurikulum berbasis proyek. Penelitian kualitatif ini mengkaji strategi guru dalam mengatasi kesenjangan kognitif siswa di kelas yang menerapkan Kurikulum Merdeka, dengan studi kasus di MA Darussalam Kota Tangerang Selatan Provinsi Banten kelas 10. Melalui wawancara mendalam dengan 1 guru PAI dan 1 kepala sekolah, serta observasi pembelajaran, penelitian mengidentifikasi empat strategi efektif: (1) pembelajaran berdiferensiasi berbasis asesmen diagnostik, (2) asesmen formatif berkelanjutan, (3) pembelajaran berbasis proyek, dan (4) pemanfaatan teknologi pendidikan. Temuan menunjukkan peningkatan pemahaman siswa setelah tiga bulan implementasi, dengan faktor kunci berupa umpan balik personal, tutor sebaya, dan perubahan mindset siswa. Kendala utama meliputi keterbatasan waktu persiapan materi dan kebutuhan pelatihan guru berkelanjutan. Implikasi penelitian menekankan pentingnya: (1) pengembangan komunitas praktik guru, (2) integrasi teknologi dalam asesmen, dan (3) kebijakan sekolah yang mendukung fleksibilitas pedagogis. Temuan ini memberikan kerangka operasional bagi guru dalam mengelola kelas heterogen sesuai prinsip Kurikulum Merdeka, sekaligus memperkaya model pembelajaran berdiferensiasi dengan kontekstualisasi lokal. Penelitian merekomendasikan pengembangan modul pelatihan terintegrasi platform digital untuk optimalisasi strategi penanganan kesenjangan kognitif.